(untitled) (Detroit, 2006)
Chemical compounds includes 180 entries on both organic and inorganic compounds, including acids, vitamins, polymers, medications, industrial chemicals, and more.
Keywords: Chemicals,Organic compounds,Inorganic compounds,Hóa học,Hợp chất hữu cơ,Hợp chất vô cơ